2005
DOI: 10.1159/000087174
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Monolateral Nerve-Sparing Radical Prostatectomy in Selected Patients

Abstract: Introduction: In recent years there has been a shift in prostate cancer stage with the majority of patients nowadays being operated with cT1c disease, prostate-specific antigen levels of <10 ng/ml, and a decreased rate of seminal vesicle invasion. Recent data suggest the role of preservation of the seminal vesicle in improving continence and/or potency. We describe our preliminary experience with seminal-sparing, unilateral nerve-sparing retropubic radical prostatectomy. Patients and Methods: 21 selected patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
1
10
0
2
Order By: Relevance
“…Sparing the tips of the seminal vesicles in patients who are at minimal risk of seminal vesicle involvement by cancer has been suggested to improve both continence and erections. [13][14][15][16] Our study have confirmed the intimate relationship between the tips of the seminal vesicles and the IHP: the IHP travels along the lateral aspect of the seminal vesicle and forms a surgical plane with seminal vesicle. The seminal vesicle tip-sparing technique avoids any traction and dissection damage to the IHP.…”
Section: Ihp and Seminal Vesicle Preservationsupporting
confidence: 76%
“…Sparing the tips of the seminal vesicles in patients who are at minimal risk of seminal vesicle involvement by cancer has been suggested to improve both continence and erections. [13][14][15][16] Our study have confirmed the intimate relationship between the tips of the seminal vesicles and the IHP: the IHP travels along the lateral aspect of the seminal vesicle and forms a surgical plane with seminal vesicle. The seminal vesicle tip-sparing technique avoids any traction and dissection damage to the IHP.…”
Section: Ihp and Seminal Vesicle Preservationsupporting
confidence: 76%
“…Thus, if resection of the tip of the SV is not oncologically necessary, it would seem wise to spare it. However, the benefits and the risks of SV tip preservation are subject to considerable uncertainty [30][31][32][33][34][35]. There are no good estimates of the degree to which SV sparing improves function and similarly we have no good estimates of the degree to which SV preservation increases the risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have suggested that sparing the tip of these structures would decrease erectile and urinary dysfunction [69]. Three small retrospective studies have demonstrated improved functional outcomes following seminal vesicle-sparing surgery [68]. In a fourth study, Albers et al randomly subjected patients with localized prostate cancer either to a seminal vesicle-sparing approach or to a radical prostatectomy with complete seminal vesicle removal.…”
Section: Introductionmentioning
confidence: 99%